Мектепке шекемги жастағы балаларда операциялық ойлаўды қәлиплести- риўдиң психологиялық айрықшалықлары - Уразимова, Т.В (ILIM hám JÁMIYET, 2024)
The article is devoted to the problem of psychological characteristics of the formation of operational thinking in pre- school children. The age-related characteristics of children's operational intelligence are considered.